Using Barron’s Toeic Preparation Course Package To Improve The Listening Skill For Vocational School - Umar Umar (Universitas Negeri Makassar, 2017)
This research aims at finding out the use of Barron’s TOEIC preparation course package to improve the listening of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011.The objectives of the research were to find out whether or not the use of Barron’s TOEIC preparation course package significantly improves the listening ability of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011.The research used quasi experimental research design. The samples consisted of 50 students which belonged to two groups; experimental group and control group. The research data were collected using two the listening test was given to the both groups. The research results indicated that the use of Barron’s TOEIC preparation course package significantly improved the listening ability of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011. The results of posttest of both groups were improved, but the use of Barron’s TOEIC preparation course package was more improved than English in Progress Business & Management for SMK Year XI: TOEIC based Activities, By Munash F. Anwar. It was proved by the result of mean score of posttest of the experimental was higher than the control group in listening (85.00 > 79.40).